PENINGKATAN PENGETAHUAN MENGENAI STUNTING DI DESA TALAGA, PUSKESMAS CIKUPA - Atzmardina, Zita; Bramasta, Arya Adi; Wulandari, Dhea Asih; Grace, Jennifer; Charity Kamalo, Angelica Joanna (Jurnal Serina Abdimas, 2024)
Stunting is defined as a condition of failure to thrive in children aged less than five years, usually called toddlers, due to chronic malnutrition and recurrent infections, especially during the First 1000 Days of Life (HPK). Data on toddlers in Banten province shows that 3.5% are severely underweight and 14.2% are underweight. This data is higher than the national data, which recorded 3% who were severely underweight and 12.9% who were underweight. The number of stunting cases in the Cikupa Community Health Center working area in 2022 was 116 cases and in 2023 there were 127 stunting cases with the highest cases being in Talaga Village, namely an increase of 17 cases. The aim of this activity is to increase knowledge about stunting so that it can reduce the number of cases. To identify problems, the Blum Paradigm and Fishbone Diagram are used to determine the root cause of the problem. The results of identifying problems using the Blum Paradigm revealed lifestyle factors that play a role in the high number of tuberculosis cases. The results of the activity showed that 91% of participants scored >70 points on the post-test and 5 participants who were called randomly were able to practice good and correct hand hygiene and use a balanced nutritional food menu according to the contents of my plate. Based on the intervention we carried out, it can be stated that our intervention was successful so it is hoped that it can reduce stunting cases in the Cikupa Community Health Center working area. ABSTRAK Stunting didefinisikan sebagai suatu kondisi gagal tumbuh pada anak yang berusia kurang dari lima tahun yang biasa disebut Balita dikarenakan kekurangan gizi kronis serta akibat infeksi berulang terutama pada periode 1000 Hari Pertama Kehidupan (HPK). Data Balita di provinsi Banten terdapat 3,5 % yang mengalami severely underweight dan 14,2 % yang mengalami underweight. Data tersebut lebih tinggi dari nasional yang mencatat ada 3 % yang mengalami severely underllweight dan 12,9 % yang mengalami underweight. Jumlah kasus stunting pada wilayah kerja Puskesmas Cikupa tahun 2022 adalah 116 kasus dan pada tahun 2023 adalah 127 kasus stunting dengan kasus tertinggi berada di Desa Talaga yaitu terjadi peningkatan sebanyak 17 kasus. Tujuan dilakukan kegiatan ini untuk meningkatkan pengetahuan mengenai stunting sehingga dapat menurunkan jumlah kasus. Untuk identifikasi masalah digunakan Paradigma Blum dan Diagram fishbone untuk menentukan akar penyebab masalah. Hasil identifikasi masalah dengan Paradigma Blum didapatkan faktor lifestyle yang berperan pada tingginya kasus tuberkulosis. Hasil kegiatan didapatkan 91% peserta mendapatkan nilai >70 poin pada post-test dan 5 peserta yang dipanggil secara acak dapat mempraktikkan Hand Hygiene yang baik dan benar serta menggunakan menu makanan gizi seimbang sesuai Isi Piringku. Berdasarkan intervensi yang kami lakukan dapat dinyatakan intervensi kami berhasil sehingga diharapkan dapat menurunkan kasus stunting di wilayah kerja Puskesmas Cikupa